Design and Economic Study for Use the Photovoltaic Systems for Electricity Supply in Isfahan Museum Park - Hossein Shahinzadeh; Mohammad Moien Najaf Abadi; Mohammad Hajahmadi; Ali Paknejad (International Journal of Power Electronics and Drive Systems (IJPEDS), 2013)
Electricity production is one of the country's economic strength foundations. Therefore, it has been considered to increase electricity production and it’s value-added in recent decades. In this respect, with the orientation and access to advanced technology, application and use of clean energy and renewable systems has considerable development for human energy needed. Ease of access and use of solar energy has placed it in proper position. The sun is the largest source of earth's energy supply which energy issued from it, is used by different ways to provide energy needed (fossil fuels and non-fossil). When we know that the solar radiation energy using photovoltaic systems directly and without intermediates is converting into electrical energy, it will be more important in the energy conversion systems. In this paper the during introducing of photovoltaic systems as a new energy systems, they are described types of photovoltaic cells and its applications. Also It examines the economic issues in the power supply in Isfahan Museum Park.DOI: http://dx.doi.org/10.11591/ijpeds.v3i1.1797